Skabies dengan Infeksi Sekunder Pada Sindrom Down - Mitha Yunda Pertiwi; Dedianto Hidajat (Faculty of Medicine Universitas Mataram, 2022)
Scabies is a skin disease caused by Sarcoptes scabiei. The signs and symptoms of scabies such as pruritus and skin lesions in the form of small papules with canaliculus and escoriations. If it’s not treated, complications may occur. The most common complication is secondary infection. The principles in the management of scabies are eradicating mites with pharmacological therapy, preventing the spread of scabies, and overcoming complications. A 1-year-7-month-old child with down syndrome was consulted to the dermatovenereology clinic of RSUDP NTB with complaints of lesion since 1 month ago in the buttocks, genital, between the toes and soles, between the fingers and palms, and around the chest. The patient scratches the spots at night. The patient’s father, mother and brother experiencing similar complaints. Localized status of skin lesions are on the buttocks, external genitalia, thorax, between the fingers and toes, as well as the palms of the hands and feet. The description of lesions were papules with grayish white canaliculus, well-defined, lenticular shape, multiple, discrete arrangement, and regional distribution with scales. In addition, there are white pustules, well-defined, miliary shape, multiple, discrete arrangement, and regional distribution with crusts. The diagnosis of this patient was clinical scabies with secondary infection. The patient was given causative, symptomatic and secondary infection therapy. In addition, to treat patients, the family approach has an important role in eradicating scabies.